Electrolyte additive and application thereof

By using electrolyte additives with specific structural formulas in lithium metal batteries, alloys are formed to reduce the generation of lithium dendrites, and the SEI film rich in metal oxides is decomposed to solve the problem of battery performance degradation caused by lithium dendrites, and the battery cycle stability and Coulomb efficiency are achieved.

CN119812470APending Publication Date: 2025-04-11XINYU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411988423.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The growth of lithium dendrites in lithium metal batteries leads to a reduced efficiency of battery curloss and a shorter cycle life, and may cause short circuits and combustion explosions, seriously hindering the practical application of lithium-S batteries and other lithium-containing metal batteries.

Method used

Using an electrolyte additive, including a compound of a specific structural formula, the formation of lithium dendrites is guided to be deposited inside the electrolyte by forming an alloy with the metal salt in the electrolyte, thereby reducing the formation of lithium dendrites. In addition, the electrolyte contains metal ions, which can decompose and form a solid electrolyte interface film (SEI) rich in LiF, LiCl, Li3N, LiNOx, LiCO3, and Li2O on the surface of the negative electrode, thereby improving the toughness of the SEI film and further inhibiting the growth of lithium dendrites.

Benefits of technology

It effectively improves the interface status of the battery, inhibits the growth of lithium dendrites, and significantly improves the cycle stability performance and Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812470A_ABST
    Figure CN119812470A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte additive and application thereof, and belongs to the technical field of secondary batteries. According to the invention, the compound # imgabs0 # shown in the structural general formula is used as an additive to be added into an electrolyte, and then the additive is used for a solid electrolyte to coat a corresponding lithium metal negative electrode, or is used as a liquid electrolyte additive to prepare a battery, and the additive can effectively improve the interface condition of the battery and inhibit the growth of lithium dendrites of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to an electrolyte additive and application thereof. Background Art

[0002] The improvement of the performance of energy storage devices can effectively promote the application of new energy. Among the various energy storage devices, electrochemical energy storage batteries have become one of the important research directions in countries around the world due to their high energy density, good energy conversion efficiency, low pollution, easy combination and mobility.

[0003] Among various electrochemical energy storage batteries, lithium metal anode has high capacity (3860mA hg -1 ), as graphite (theoretical capacity is 372 mA hg -1 ) have been widely studied and are considered the most promising negative electrode materials for lithium-ion batteries. The energy density of batteries with lithium metal negative electrodes and sulfur positive electrodes, a ternary positive electrode, can be as high as 700Wh / kg, and has very bright application prospects. However, the growth of lithium dendrites will lead to a series of problems such as pulverization of lithium metal electrodes, generation of dead lithium, reduced coulombic efficiency of batteries and shortened cycle life; the growth of lithium dendrites will also pierce the diaphragm, causing battery short circuits and even combustion and explosion, which seriously hinders the practical application of lithium metal batteries such as Li-S batteries. In addition, metal Na batteries, metal K batteries and metal Zn batteries will also encounter dendrite growth problems, which will also affect the cycle life and safety performance of these batteries. Summary of the invention

[0004] The invention proposes an electrolyte additive and application thereof, aiming to solve the problem that lithium dendrites are easily grown on the negative electrode of the existing alkali metal or alkaline earth metal battery.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical objectives of the present invention is to provide an electrolyte additive, including a compound shown in the following structural formula I, II or III:

[0007]

[0008] Wherein: R1, R2, R3 are each independently selected from a hydrocarbon or halogenated hydrocarbon containing at least one carbon atom;

[0009] M is one of Zn, Sn, Si, Al, Ge and In;

[0010] A is one of N, P, S, B, Cl, I and Br;

[0011] D is one of O, F and Cl;

[0012] n is any integer from 1 to 4.

[0013] In the additive provided by the present invention, M in the general structural formulas Ⅰ-Ⅲ will form an alloy with the metal salt in the electrolyte, and the alloy will guide the metal to be deposited inside the electrolyte, thereby reducing the generation of lithium dendrites.

[0014] Furthermore, R1, R2, and R3 are independently selected from hydrocarbons or halogenated hydrocarbons with 1-16 carbon atoms.

[0015] Furthermore, the general structural formula I includes at least one of the compounds shown in the following structures:

[0016]

[0017] The general structural formula II comprises at least one of the compounds represented by the following structures: Zn(ClO4)2, Zn(NO3)2 or Zn(BF4)2; and / or

[0018] The general structural formula III includes at least one In(OOCCF3)4 or Zn(OOCCF3)2 of the compounds shown in the following structures.

[0019] The second technical purpose of the present invention is to provide an electrolyte, which includes the electrolyte additive, a solvent and an electrolyte salt.

[0020] The M in the structural formula I-III contained in the additive provided by the present invention will form a metal alloy with the metal (Li, Na or K) in the electrolyte salt, and the alloy can induce the 3D deposition of metal ions below the solid electrolyte interface (SEI) film, reducing the possibility of metal ions depositing perpendicular to SEI, thereby inhibiting the growth of lithium dendrites. In addition, the solid electrolyte contains metal ions, which can decompose on the surface of the negative electrode to form a rich LiF, LiCl, Li3N, LiNO x , LiCO3, and Li2O SEI, thereby improving the toughness of the SEI film and further inhibiting the growth of lithium dendrites.

[0021] Furthermore, the content of the electrolyte additive in the electrolyte is 0.1-30 wt %.

[0022] Furthermore, the electrolyte includes a polymer solid electrolyte, an organic-inorganic solid electrolyte and a liquid electrolyte.

[0023] Furthermore, the polymer solid electrolyte includes one of poly 1,3-dioxolane (PDOL) and polyethylene oxide (PEO), and the electrolyte contains at least one of LiTFSI, LiFSI, LiNO3, LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiPF2, LiHFDF, NaTFSI, KTFSI and cyclic imide salts; and / or

[0024] The organic-inorganic solid electrolyte comprises one of PDOL-lithium dysprosium tantalum oxide (LLTO) solid electrolyte and PDOL-lithium lanthanum zirconium oxide (LLZO), and the electrolyte contains at least one of LiTFSI, LiFSI, LiNO3, LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiPF2, LiHFDF, NaTFSI, KTFSI and cyclic imide salts; and / or

[0025] The solvent in the liquid electrolyte includes at least one of a fluorinated solvent, ethylene glycol dimethyl ether, dimethyl carbonate, 1,3-dioxolane, vinylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, propylene sulfite, methyl propionate, polyethylene oxide and dimethylacetamide, wherein the fluorinated solvent includes at least one of fluoroethylene carbonate, 3,3,3-trifluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether and tris(2,2,2-trifluoroethyl)phosphite.

[0026] Further, the electrolyte salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium perchlorate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(monofluoromethylsulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide, sodium bis(trifluoromethylsulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, potassium bis(fluorosulfonyl)imide, bis(trifluoromethyl ... At least one of zinc fluoromethanesulfonyl imide, zinc bis(fluorosulfonyl)imide, sodium bis(fluorosulfonyl)imide, potassium bis(fluorosulfonyl)imide, zinc bistrifluoromethanesulfonyl imide, zinc bis(fluorosulfonyl)imide and cyclic imide salts; wherein the cyclic imide salt includes at least one of 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide lithium, 1,1,2,2-tetrafluoroethane-1,3-disulfonic acid imide lithium and 1,1,2,2,3,3,4,4-octafluorobutane-1,3-disulfonic acid imide lithium.

[0027] The third technical purpose of the present invention is to provide an electrolyte including the electrolyte.

[0028] Furthermore, the electrolyte also includes nitrate; the nitrate includes LiNO3 or NaNO3.

[0029] A fourth technical purpose of the present invention is to provide a secondary battery, comprising a negative electrode material, a positive electrode material, a separator and the electrolyte.

[0030] The secondary battery contains the electrolyte, which can effectively improve the interface condition of the battery, inhibit the growth of lithium dendrites in the battery, and thus greatly improve the cycle performance of the battery.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The content of the additive provided by the present invention in the electrolyte is 0.1-30wt%. The electrolyte additive can effectively improve the interface condition of the battery, inhibit the growth of lithium dendrites of the battery, and thus improve the cycle stability performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 A schematic diagram of the coulombic efficiency test results of the Li-Cu battery provided in Example 1 and Comparative Example 1 during the charge and discharge cycle;

[0035] Figure 2 A schematic diagram of voltage curve test results of the Li-Li symmetrical battery provided in Example 13 and Comparative Example 2 during the charge and discharge cycle;

[0036] Figure 3 A schematic diagram of the battery capacity, battery coulombic efficiency and cycle performance results during the charge and discharge process of the Li-S battery provided in Example 14 and Comparative Example 3;

[0037] Figure 4 This is a SEM image of the lithium negative electrode surface after the Li@PDOL-1-Li@PDOL-1 symmetric battery in Example 13 was cycled 50 times;

[0038] Figure 5 This is a SEM image of the lithium negative electrode surface after the Li-Li symmetric battery in Comparative Example 2 was cycled 50 times. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0043] In the present invention, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0044] In the present invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple.

[0045] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0046] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0047] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0048] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the embodiments of the present invention, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0050] The present invention provides an electrolyte additive, comprising a compound represented by the following structural formula I, II or III:

[0051]

[0052] Wherein: R1, R2, and R3 are each independently selected from a hydrocarbon or halogenated hydrocarbon containing at least one carbon atom; these hydrocarbons may be connected to each other to form a ring, or may not be connected to each other;

[0053] M is one of Zn, Sn, Si, Al, Ge and In;

[0054] A is one of N, P, S, B, Cl, I and Br;

[0055] D is one of O, F and Cl;

[0056] n is any integer from 1 to 4.

[0057] In some embodiments of the present invention, the R1, R2, and R3 are independently selected from hydrocarbons or halogenated hydrocarbons with a carbon number of 1-16. Wherein, the hydrocarbons include alkanes, alkynes or aromatic hydrocarbons, and when aromatic hydrocarbons are selected, the carbon number is 6-12. The halogenated hydrocarbons include partially halogenated or fully halogenated, and the halogen elements include at least one of F, Cl, Br and I. In the embodiments of the present invention, by using halogen elements to replace part or all of the hydrogen of R1, R2, and R3 in the additive structural formulas Ⅰ and Ⅲ, and using N, P, S, B, Cl, I or Br to replace part or all of the hydrogen of A in the additive structural formula Ⅱ, the generated lithium compound can be attached to the surface of the lithium dendrite seed to repel the enrichment of lithium ions on the surface of the lithium dendrite seed, thereby inhibiting the formation of lithium dendrites.

[0058] In some embodiments of the present invention, the general structural formula II is an inorganic salt of Zn, Sn, Si, Al, Ge and In.

[0059] In some embodiments of the present invention, the general structural formula III is an organic salt of Zn, Sn, Si, Al, Ge and In.

[0060] In some embodiments of the present invention, the additive includes at least one of the compounds shown in the following structures:

[0061]

[0062] The present invention also provides an electrolyte, the electrolyte comprising the above electrolyte additive, a solvent and an electrolyte salt. The electrolyte may be a liquid electrolyte, a polymer solid electrolyte or an inorganic solid electrolyte. Exemplarily, the present invention provides a polymer solid electrolyte, comprising the above additive, a solvent and an electrolyte salt.

[0063] In some embodiments of the present invention, the content of the electrolyte additive in the electrolyte is 0.1-30wt%. Exemplarily, in the following embodiments of the present invention, the content of the electrolyte additive in the electrolyte may include but is not limited to 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt% or any range between the foregoing ratios.

[0064] In the case where the additive can be quickly dissolved, increasing the content of the additive in the electrolyte can increase the stable cycle times of the battery, but when the content of the additive in the electrolyte is too high, it will affect the solubility of the additive in the electrolyte, which is not conducive to increasing the stable cycle times of the battery. In other words, the content of the additive in the electrolyte can be adjusted according to whether the additive can be quickly dissolved in the electrolyte.

[0065] In some embodiments of the present invention, the electrolyte includes a polymer solid electrolyte, an organic-inorganic solid electrolyte and a liquid electrolyte.

[0066] In some embodiments of the present invention, the polymer solid electrolyte includes one of poly 1,3-dioxolane (PDOL) and polyethylene oxide (PEO), and the electrolyte contains at least one of LiTFSI, LiFSI, LiNO3, LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiPF2, LiHFDF, NaTFSI, KTFSI and cyclic imide salts; and / or

[0067] In some embodiments of the present invention, the organic-inorganic solid electrolyte includes one of PDOL-lithium dysprosium tantalum oxide (LLTO) solid electrolyte and PDOL-lithium lanthanum zirconium oxide (LLZO), and the electrolyte contains at least one of LiTFSI, LiFSI, LiNO3, LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiPF2, LiHFDF, NaTFSI, KTFSI and cyclic imide salts.

[0068] In some embodiments of the present invention, the solvent in the liquid electrolyte specifically includes at least one of a fluorinated solvent, ethylene glycol dimethyl ether (DME), dimethyl carbonate (DMC), 1,3-dioxolane (DOL), vinylene carbonate, propylene carbonate, ethylene carbonate (EC), diethyl carbonate, ethyl methyl carbonate, methyl propylene sulfite propionate, polyethylene oxide (PEO) and dimethylacetamide (DMAC). Among them, the fluorinated solvent includes but is not limited to at least one of fluoroethylene carbonate (FEC), 3,3,3-trifluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether (alias: 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether) and tris (2,2,2-trifluoroethyl) phosphite (TTFP). Polyethylene oxide is a powder, so it needs to be mixed and dissolved with dimethylacetamide as a solvent. For example, in the following examples of the present invention, a mixture of 1,3-dioxolane and ethylene glycol dimethyl ether, a mixture of ethylene carbonate and dimethyl carbonate, and a mixture of polyethylene oxide and dimethylacetamide were selected as solvents to verify the effects.

[0069] In some embodiments of the present invention, the electrolyte salt is not limited to LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium bis(oxalatoborate), LiClO4 (lithium perchlorate), LiCF3SO3 (lithium trifluoromethanesulfonate), LiODFB (lithium difluorooxalatoborate), LiN(SO2CF3)2 (lithium bis(trifluoromethylsulfonyl)imide), LiN(SO2F)2 (lithium bis(monofluoromethylsulfonyl)imide, also written as LiN(CF3SO2)2), LiTFSI (bis(trifluoromethylsulfonyl)imide), LiN(SO2CF3)2 (lithium bis(monofluoromethylsulfonyl)imide, also written as LiN(CF3SO2)2), LiTFSI (lithium trifluoromethanesulfonate), LiN(SO2CF3)2 (lithium bis(trifluoromethylsulfonyl)imide, also written as LiN(CF3SO2)2), LiN(SO2CF3)2 (lithium bis(mono ... At least one of lithium bis(trifluoromethylsulfonyl)imide (LiFSI), LiHFDF (lithium 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide), NaTFSI (sodium bis(trifluoromethylsulfonyl)imide), KTFSI (potassium bis(trifluoromethylsulfonyl)imide), sodium bis(fluorosulfonyl)imide (NaFSI), potassium bis(fluorosulfonyl)imide (KFSI), zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2), zinc bis(fluorosulfonyl)imide (Zn(TFSI)2) and cyclic imide salts. Wherein, the cyclic imide salt includes but is not limited to at least one of 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide lithium, 1,1,2,2-tetrafluoroethane-1,3-disulfonic acid imide lithium and 1,1,2,2,3,3,4,4-octafluorobutane-1,3-disulfonic acid imide lithium. Exemplarily, in the following embodiments of the present invention, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(fluorosulfonyl)imide (NaFSI), potassium bis(trifluoromethanesulfonyl)imide (KTFSI), potassium bis(fluorosulfonyl)imide (KFSI), zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) and zinc bis(fluorosulfonyl)imide (Zn(FSI)2) are selected as examples for effect verification.

[0070] The present invention also provides an electrolyte comprising the electrolyte.

[0071] In some embodiments of the present invention, the electrolyte further includes nitrate; the nitrate includes LiNO3 or NaNO3. Nitrate can further inhibit the shuttle effect of polysulfide, so adding nitrate on the basis of electrolyte additives can further improve the capacity utilization and cycle efficiency of lithium-sulfur batteries.

[0072] The present invention also provides a secondary battery, comprising a negative electrode material, a positive electrode material, a separator and the electrolyte. Since the secondary battery contains the newly prepared electrolyte, the shuttle effect of the battery and the growth of lithium dendrites can be effectively suppressed, thereby significantly improving the cycle stability of the battery.

[0073] In some embodiments of the present invention, the positive electrode material includes but is not limited to at least one of copper, sulfur, sulfur-containing composite materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide and ternary materials, wherein the ternary materials include but are not limited to polymers of nickel, cobalt and manganese.

[0074] The separator is located between the positive electrode material and the negative electrode material of the lithium-containing battery. The separator mainly separates the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting; in addition, it can also allow electrolyte ions to pass through.

[0075] The negative electrode material contains lithium element.

[0076] The electrolyte may contain lithium element.

[0077] The batteries in the following embodiments of the present invention can be assembled using conventional methods in the art. The specific assembly method is not a factor discussed in the present invention and will not be described in detail in the specific embodiments.

[0078] The raw materials used in the present invention are all purchased from the market.

[0079] The technical solution of the present invention is further illustrated by the following embodiments.

[0080] The following examples and comparative examples are briefly explained:

[0081] Unit M: refers to the concentration unit of a substance, and can also be expressed as mol / L, i.e. moles per liter.

[0082] The percentage of compound 1-12 refers to the final concentration of compound 1-12 in the electrolyte, specifically the mass percentage, for example, 10% of compound 1 means that the content of compound 1 in the electrolyte is 10wt%.

[0083] Coulombic efficiency, also known as discharge efficiency, refers to the ratio of the battery's discharge capacity to its charging capacity during the same cycle, that is, the percentage of discharge capacity to charging capacity.

[0084] Secondary battery: Also called a rechargeable battery or rechargeable battery, refers to a battery that can be charged and discharged repeatedly.

[0085] Examples 1-12

[0086] A method for preparing a Cu-Li battery, comprising:

[0087] Positive electrode: Copper foil is used as the substrate, and solid electrolyte is coated on the substrate. The specific method is as follows:

[0088] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 10% of compound 1 to obtain an electrolyte;

[0089] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Cu@PDOL-1.

[0090] Negative electrode: lithium foil.

[0091] Electrolyte: Select commercial 1M LiTFSI / DOL∶DME=1∶1(V∶V) and mix with nitrate. The specific operation is as follows:

[0092] Take commercial 1M LiTFSI / DOL∶DME=1∶1(V∶V), add 4wt% LiNO3 and mix to obtain an electrolyte, recorded as 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt% LiNO3.

[0093] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into batteries, which are respectively recorded as Cu@PDOL-1||Li battery. Examples 2-12 correspond to compounds 2-12 in sequence, and the obtained batteries are recorded in sequence: Cu@PDOL-2||Li battery, Cu@PDOL-3||Li battery, Cu@PDOL-4||Li battery, Cu@PDOL-5||Li battery, Cu@PDOL-6||Li battery, Cu@PDOL-7||Li battery, Cu@PDOL-8||Li battery, Cu@PDOL-9||Li battery, Cu@PDOL-10||Li battery, Cu@PDOL-11||Li battery, Cu@PDOL-12||Li battery.

[0094] The structural formula of compound 1-12 is shown below:

[0095]

[0096] Embodiment 13

[0097] A method for preparing a Li-Li symmetrical battery, comprising:

[0098] Positive electrode: Lithium foil is used as the substrate, and a solid electrolyte is coated on the substrate. The specific method is as follows:

[0099] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 10% of compound 1 to obtain an electrolyte;

[0100] (2) The electrolyte was stirred evenly and then drop-coated on the surface of lithium foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Li@PDOL-1.

[0101] Negative electrode: Lithium foil is used as the substrate, and a solid electrolyte is coated on the substrate. The specific method is as follows:

[0102] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 10% of compound 1 to obtain an electrolyte;

[0103] (2) The electrolyte was stirred evenly and then drop-coated on the surface of lithium foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Li@PDOL-1.

[0104] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0105] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as Li@PDOL-1-Li@PDOL-1 symmetric battery.

[0106] Embodiment 14

[0107] A method for preparing a S / C-Li battery, comprising:

[0108] Positive electrode: sulfur-containing composite material. The specific operation is: S and C are mixed in a mass ratio of 3:2, calcined at 155°C for 12 hours, then washed with ethanol and water, and then dried at 200°C to remove sulfur on the surface of the material to obtain a S / C composite.

[0109] Negative electrode: Li@PDOL-1, prepared by the same method as in Example 13.

[0110] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0111] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, which was denoted as S / C-Li@PDOL-1 battery.

[0112] Embodiment 15

[0113] A method for preparing a Cu-Li battery, comprising:

[0114] Positive electrode: Copper foil is used as the substrate, and solid electrolyte is coated on the substrate. The specific method is as follows:

[0115] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 1% of compound 1 to obtain an electrolyte;

[0116] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was recorded as Cu@PDOL-1-1%.

[0117] Negative electrode: lithium foil.

[0118] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0119] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, denoted as Cu@PDOL-1-1%||Li battery.

[0120] Example 16

[0121] A method for preparing a Cu-Li battery, comprising:

[0122] Positive electrode: Copper foil is used as the substrate, and solid electrolyte is coated on the substrate. The specific method is as follows:

[0123] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 5% of compound 1 to obtain an electrolyte;

[0124] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was recorded as Cu@PDOL-1-5%.

[0125] Negative electrode: lithium foil.

[0126] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0127] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, denoted as Cu@PDOL-1-5%||Li battery.

[0128] Embodiment 17

[0129] A method for preparing a Cu-Li battery, comprising:

[0130] Positive electrode: Copper foil is used as the substrate, and solid electrolyte is coated on the substrate. The specific method is as follows:

[0131] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 15% of compound 1 to obtain an electrolyte;

[0132] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was recorded as Cu@PDOL-1-15%.

[0133] Negative electrode: lithium foil.

[0134] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0135] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, denoted as Cu@PDOL-1-15%||Li battery.

[0136] Embodiment 18

[0137] A method for preparing a Cu-Li battery, comprising:

[0138] Positive electrode: Copper foil is used as the substrate, and solid electrolyte is coated on the substrate. The specific method is as follows:

[0139] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI) and 20% of compound 1 to obtain an electrolyte;

[0140] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was recorded as Cu@PDOL-1-20%.

[0141] Negative electrode: lithium foil.

[0142] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0143] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, denoted as Cu@PDOL-1-20%||Li battery.

[0144] Embodiment 19

[0145] A method for preparing a Cu-Li battery, comprising:

[0146] Positive electrode: Copper foil is used as the substrate, and solid electrolyte is coated on the surface of the substrate. The specific operation is as follows:

[0147] (1) 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was dissolved in a mixed solvent (the mixed solvent was prepared by mixing polyethylene oxide (PEO) and dimethylacetamide (DMAC) in a mass ratio of 1:10), and then 10% of compound 1 (the structural formula is the same as in Example 1, the same below) was added to obtain an electrolyte;

[0148] (2) The electrolyte was stirred evenly and then drop-coated on the surface of lithium foil and dried to obtain a polyPEO electrolyte containing compound 1, which was recorded as Cu@PEO-1.

[0149] Negative electrode: lithium foil

[0150] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0151] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as Cu-Li@Li@PEO-1 battery.

[0152] Embodiment 20

[0153] A method for preparing a Cu-Li battery, comprising:

[0154] Positive electrode: Cu@PDOL-1, prepared by the same method as in Example 1.

[0155] Negative electrode: lithium foil

[0156] Electrolyte: Dissolve 1M (LiPF6) in a mixed solvent (the mixed solvent is a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1), and use the electrolyte directly as the electrolyte, recorded as 1MLiPF6+EC:DMC=1:1.

[0157] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery.

[0158] Embodiment 21

[0159] A method for preparing a Li-LiCoO2 battery, comprising:

[0160] Positive electrode: LiCoO2.

[0161] Negative electrode: Li@PDOL-1, prepared by the same method as in Example 13.

[0162] Electrolyte: 1M LiPF6+EC∶DMC=1∶1, preparation method is the same as Example 20.

[0163] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as LiCoO2-Li@PDOL-1 battery.

[0164] Embodiment 22

[0165] A method for preparing a Li-Cu battery, comprising:

[0166] Positive electrode: Cu foil.

[0167] Negative electrode: Li foil

[0168] Electrolyte: 1M LiPF6+EC∶DMC=1∶1+5% of compound 1.

[0169] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as Li||Cu-LiPF6-10%-5 battery.

[0170] Embodiment 23

[0171] A method for preparing a Na-Na battery, comprising:

[0172] Positive electrode: Based on sodium foil, a layer of solid electrolyte is coated on the surface of the sodium foil. The method is as follows:

[0173] (1) dissolving 1 M sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M sodium bis(fluorosulfonyl)imide (NaFSI) and 10% of compound 1 to obtain an electrolyte;

[0174] (2) The electrolyte was stirred evenly and then drop-coated on the surface of sodium foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Na@PDOL-1.

[0175] Negative electrode: Based on sodium foil, a layer of solid electrolyte is coated on the surface of the sodium foil. The method is as follows:

[0176] (1) dissolving 1 M sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M sodium bis(fluorosulfonyl)imide (NaFSI) and 10% of compound 1 to obtain an electrolyte;

[0177] (2) The electrolyte was stirred evenly and then drop-coated on the surface of sodium foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Na@PDOL-1.

[0178] Electrolyte: 1M NaTFSI / DOL∶DME=1∶1(V∶V)+4wt%NaNO3, prepared by the same method as in Example 1.

[0179] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, which was denoted as Cu@PDOL-1||Na battery.

[0180] Embodiment 24

[0181] A method for preparing a KK battery, comprising:

[0182] Positive electrode: Based on potassium foil, a layer of solid electrolyte is coated on the surface of potassium foil as follows:

[0183] (1) dissolving 1 M potassium bis(trifluoromethanesulfonyl)imide (KTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M potassium bis(fluorosulfonyl)imide (KFSI) and 10% of compound 1 to obtain an electrolyte;

[0184] (2) The electrolyte was stirred evenly and then drop-coated on the surface of potassium foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as K@PDOL-1.

[0185] Negative electrode: Based on potassium foil, a layer of solid electrolyte is coated on the surface of potassium foil as follows:

[0186] (1) dissolving 1 M potassium bis(trifluoromethanesulfonyl)imide (KTFSI) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M potassium bis(fluorosulfonyl)imide (KFSI) and 10% of compound 1 to obtain an electrolyte;

[0187] (2) The electrolyte was stirred evenly and then drop-coated on the surface of potassium foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as K@PDOL-1.

[0188] Electrolyte: 1M KTFSI / DOL∶DME=1∶1(V∶V)+4wt% KNO3, prepared by the same method as in Example 1.

[0189] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, which was denoted as Cu@PDOL-1||K battery.

[0190] Embodiment 25

[0191] A method for preparing a Zn-Zn battery, comprising:

[0192] Positive electrode: Using zinc foil as the base, a layer of solid electrolyte is coated on the surface of the zinc foil as follows:

[0193] (1) dissolving 1 M zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M zinc bis(fluorosulfonyl)imide (Zn(FSI)2) and 10% of compound 1 to obtain an electrolyte;

[0194] (2) The electrolyte was stirred evenly and then drop-coated on the surface of zinc foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Zn@PDOL-1.

[0195] Negative electrode: Using zinc foil as the base, a layer of solid electrolyte is coated on the surface of the zinc foil as follows:

[0196] (1) dissolving 1 M zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) in a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M zinc bis(fluorosulfonyl)imide (Zn(FSI)2) and 10% of compound 1 to obtain an electrolyte;

[0197] (2) The electrolyte was stirred evenly and then drop-coated on the surface of zinc foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was denoted as Zn@PDOL-1.

[0198] Electrolyte: 1M Zn(TFSI)2 / DOL∶DME=1∶1(V∶V)+4wt% Zn(NO3), preparation method is the same as Example 1.

[0199] Battery assembly: The above positive electrode, negative electrode and electrolyte were conventionally assembled into a battery, which was denoted as Cu@PDOL-1||Zn battery.

[0200] Embodiment 26

[0201] A method for preparing a Li-Li battery, comprising:

[0202] Positive electrode: Lithium foil is used as the substrate, and a solid electrolyte is coated on the substrate. The specific method is as follows:

[0203] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) into a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI), 10% of compound 1 and 50% by mass of lithium lanthanum zirconium oxide to obtain an electrolyte;

[0204] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was recorded as Cu@LLZO-PDOL-1.

[0205] Negative electrode: Lithium foil is used as the substrate, and a solid electrolyte is coated on the substrate. The specific method is as follows:

[0206] (1) dissolving 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) into a mixed solvent (the mixed solvent is prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then adding 1 M lithium bis(fluorosulfonyl)imide (LiFSI), 10% of compound 1 and 50% by mass of lithium lanthanum zirconium oxide to obtain an electrolyte;

[0207] (2) The electrolyte was stirred evenly and then drop-coated on the surface of copper foil and dried to obtain a poly 1,3-dioxolane electrolyte containing compound 1, which was recorded as Cu@LLZO-PDOL-1.

[0208] Electrolyte: Mix the electrolyte and nitrate. The specific operation is as follows:

[0209] 1M of the electrolyte prepared in step (1) was mixed with 4wt% of LiNO3 to obtain an electrolyte solution, recorded as 1MLiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3.

[0210] Comparative Example 1

[0211] A method for preparing a Cu-Li battery, comprising:

[0212] Positive electrode: Cu foil.

[0213] Negative electrode: lithium foil.

[0214] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0215] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is recorded as a Cu-Li battery.

[0216] Comparative Example 2

[0217] A method for preparing a Li-Li battery, comprising:

[0218] Positive electrode: lithium foil.

[0219] Negative electrode: lithium foil.

[0220] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0221] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is recorded as a Li-Li battery.

[0222] Comparative Example 3

[0223] A method for preparing a S / C-Li battery, comprising:

[0224] Positive electrode: S / C composite, prepared by the same method as in Example 14.

[0225] Negative electrode: lithium foil.

[0226] Electrolyte: 1M LiTFSI / DOL∶DME=1∶1(V∶V)+4wt%LiNO3, prepared by the same method as in Example 1.

[0227] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is recorded as an S / C composite battery.

[0228] Comparative Example 4

[0229] A method for preparing a Cu-Li battery, comprising:

[0230] Positive electrode: Cu foil.

[0231] Negative electrode: lithium foil.

[0232] Electrolyte: 1M LiPF6+EC∶DMC=1∶1, preparation method is the same as Example 20.

[0233] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is recorded as a Cu-Li battery.

[0234] Comparative Example 5

[0235] A method for preparing a LiCoO2-Li battery, comprising:

[0236] Positive electrode: LiCoO2.

[0237] Negative electrode: lithium foil.

[0238] Electrolyte: 1M LiPF6+EC∶DMC=1∶1, preparation method is the same as Example 20.

[0239] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as a LiCoO2-Li battery.

[0240] Comparative Example 6

[0241] A method for preparing a Na-Na battery, comprising:

[0242] Positive electrode: Na foil.

[0243] Negative electrode: sodium foil.

[0244] Electrolyte: 1 M sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) was dissolved in a mixed solvent (the mixed solvent was prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then 1 M sodium bis(fluorosulfonyl)imide (NaFSI) and 10% of compound 1 were added to obtain an electrolyte;

[0245] 1M electrolyte was mixed with 4wt% NaNO3 to obtain an electrolyte solution, recorded as 1M NaTFSI / DOL∶DME=1∶1(V∶V)+4wt% NaNO3.

[0246] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as a Na-Na battery.

[0247] Comparative Example 7

[0248] A method for preparing a KK battery, comprising:

[0249] Positive electrode: Potassium foil.

[0250] Negative electrode: Potassium foil.

[0251] Electrolyte: 1 M potassium bis(trifluoromethanesulfonyl)imide (KTFSI) was dissolved in a mixed solvent (the mixed solvent was prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then 1 M potassium bis(fluorosulfonyl)imide (KFSI) and 10% of compound 1 were added to obtain an electrolyte;

[0252] 1M electrolyte was mixed with 4wt% KNO3 to obtain an electrolyte solution, recorded as 1M KTFSI / DOL∶DME=1∶1(V∶V)+4wt% KNO3.

[0253] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as a KK battery.

[0254] Comparative Example 8

[0255] A method for preparing a Zn-Zn battery, comprising:

[0256] Positive electrode: zinc foil.

[0257] Negative electrode: zinc foil.

[0258] Electrolyte: 1 M zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) was dissolved in a mixed solvent (the mixed solvent was prepared by mixing 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1), and then 1 M zinc bis(fluorosulfonyl)imide (Zn(FSI)2) and 10% of compound 1 were added to obtain an electrolyte;

[0259] 1M electrolyte was mixed with 4wt% Zn(NO3)2 to obtain an electrolyte solution, recorded as 1M Zn(TFSI)2 / DOL∶DME=1∶1(V∶V)+4wt% Zn(NO3)2.

[0260] Battery assembly: The above positive electrode, negative electrode and electrolyte are conventionally assembled into a battery, which is denoted as a Zn-Zn battery.

[0261] The secondary batteries provided in Examples 1-24 and Comparative Examples 1-10 were subjected to charge and discharge stability cycle tests, and the results are shown in Table 1.

[0262] Table 1

[0263]

[0264]

[0265]

[0266]

[0267] Note: The mass percentage concentration in Table 1 refers to the mass percentage of the corresponding compound in the entire electrolyte; the number of stable cycles refers to the number of cycles when the coulomb efficiency of the battery is ≥ 98% after cycling; the ratios in each electrolyte solvent are volume ratios.

[0268] By comparing Examples 1-12 and Comparative Example 1, it can be seen that when the solid electrolyte containing compounds 1-12 is coated on copper foil to prepare a Cu-Li battery, the battery cycle performance is significantly improved, indicating that the solid electrolyte can effectively inhibit the growth of lithium dendrites and improve the coulombic efficiency of the Li-Cu battery.

[0269] By comparing Examples 1, 15-18 and Comparative Example 1, it can be seen that when solid electrolytes containing different amounts (1-20%) of Compound 1 are coated on copper foil to prepare Cu-Li batteries, the battery cycle performance is significantly improved, and the best effect is achieved when the content of Compound 1 is 10%. This indicates that solid electrolytes coated with different contents of Compound 1 can effectively inhibit the growth of lithium dendrites and improve the coulombic efficiency of Li-Cu batteries, and the best effect is achieved when the content is 10%.

[0270] By comparing Example 13 with Comparative Example 2, it can be seen that coating the surface of metallic lithium with a solid electrolyte containing 10% of Compound 1 can effectively inhibit the growth of lithium dendrites and improve the cycle performance of the Li-Li symmetric battery.

[0271] By comparing Example 14 with Comparative Example 3, it can be seen that when a solid electrolyte containing 10% of Compound 1 is coated on the surface of metallic lithium and used as the negative electrode of a Li-S battery, the growth of lithium dendrites can be effectively inhibited, and the battery cycle performance and coulombic efficiency can be improved.

[0272] By comparing Example 19 and Comparative Example 1, it can be seen that the Cu@PEO-1||Li battery prepared by using Compound 1 in PEO solid electrolyte and coating it on the surface of copper foil has a significantly improved cycle life compared with the Cu||Li battery of Comparative Example 1, indicating that Compound 1 can be used in other solid electrolytes and coated on the surface of the electrode to effectively inhibit the growth of lithium dendrites.

[0273] By comparing Example 20 with Comparative Example 4, it can be seen that when the PDOL solid electrolyte containing Compound 1 is coated on the copper foil and other electrolytes are used, the growth of lithium dendrites can be effectively inhibited and the battery cycle performance can be improved.

[0274] By comparing Example 21 and Comparative Example 5, it can be seen that the cycle performance of LiCoO2||Li@PEO-1 prepared by coating the lithium foil with PEO solid electrolyte containing compound 1 is significantly improved compared with the battery of Comparative Example 5 LiCoO2||Li, indicating that coating the lithium foil with PEO solid electrolyte containing compound 1 can inhibit the growth of dendrites and improve the battery cycle performance.

[0275] By comparing Example 22 and Comparative Example 4, it can be seen that adding Compound 1 to the electrolyte can also effectively inhibit the growth of lithium dendrites and improve the battery cycle performance.

[0276] Combining the results of Examples 23-25 ​​and Comparative Examples 6-8, it can be seen that the electrode material and the electrolyte do not contain lithium elements, but an additive containing compound 1 is added to the solid electrolyte and coated on the surface of the corresponding metal electrode. The cycle performance of the symmetrical battery is significantly improved, indicating that coating the solid electrolyte containing compound 1 on the surface of the metal electrode can effectively inhibit the growth of dendrites.

[0277] Combining the results of Example 26 and Comparative Example 2, it can be seen that coating PDOL containing compound 1 and LLZO organic-inorganic solid electrolyte on lithium foil to prepare a lithium-lithium symmetric battery can effectively inhibit the growth of lithium dendrites and improve the battery cycle performance.

[0278] The performance test results of the secondary battery provided in the embodiments of the present application are as follows:

[0279] The Li-Cu batteries prepared in Example 1 and Comparative Example 1 were heated at 2 mA / cm 2 At a current density of 1.5, the deposition and stripping were performed for 1 h. The results of testing the coulombic efficiency of Li-Cu batteries during the charge and discharge cycle are as follows: Figure 1 As shown in a, Figure 1 The horizontal axis is the number of cycles, and the vertical axis is the Coulomb efficiency (%). Figure 1 In a, PDOL-1 refers to an electrolyte coated with poly-POL containing compound 1. Figure 1 As can be seen from a, the coulombic efficiency of the Li-Cu battery without PDOL-1 coating drops rapidly after 20 charge-discharge cycles, while the coulombic efficiency of the Li-Cu battery coated with poly POL containing compound 1 remains above 98% after 290 charge-discharge cycles. 2 At a current density of 1.5, the deposition and stripping were performed for 1 h. The results of testing the coulombic efficiency of Li-Cu batteries during the charge and discharge cycle are as follows: Figure 1 As shown in Figure b, the Li-Cu battery coated with poly POL containing compound 1 can maintain a coulombic efficiency of more than 98% after 550 cycles, while the coulombic efficiency of the uncoated bare copper is reduced to 98% after 170 cycles, indicating that the coating of the polymer electrolyte containing compound 1 can effectively improve the interface condition of the battery and inhibit the growth of lithium dendrites in the battery.

[0280] The electrolytes of Example 13 and Comparative Example 2 were used in Li-Li symmetrical batteries at 2 mA / cm 2At a current density of 1.5, the deposition and stripping were performed for 1 h, and the voltage curve of the Li-Li symmetric battery during the charge and discharge cycle was tested. Figure 2 The Li@PDOL||Li@PDOL prepared in Example 13 and Comparative Example 2 are Li-Li symmetric batteries. 2 The voltage curves of deposition and stripping during the 1h charge-discharge cycle at a current density of . Figure 2 The horizontal axis is time (in hours), and the vertical axis is voltage (in V). Figure 2 It can be seen that when the lithium sheet without PDOL-1 coating (W / oPDOL-1 in the figure) is used in Comparative Example 2, polarization occurs rapidly after the Li-Li symmetric battery is cycled for 300 hours; while when the symmetric battery with PDOL-1 coating (Li@PDOL-1-Li@PDOL-1) is used in Example 2, polarization occurs rapidly after the Li-Li symmetric battery is cycled for 300 hours. Figure 2 The lithium sheet (denoted as With PDOL-1) in the figure has not been polarized after the Li-Li symmetric battery has been cycled for 1100 hours, which further illustrates that coating with PDOL-1 can effectively improve the interface condition of the battery and inhibit the growth of lithium dendrites in the battery.

[0281] The electrolytes of Example 14 and Comparative Example 3 were used to equip Li-S batteries for electrochemical testing. Figure 3 The electrochemical performance curves of Li@PDOL||S prepared in Example 14 and Comparative Example 3 during the charge-discharge cycle at a current density of 0.4C (670 mA / g). The Li-S loading is >1 mg cm -2 , the electrolyte dosage is less than 10μL·mg -1 , Li-S battery performance Figure 3 As shown, Figure 3 The horizontal axis is the number of cycles, and the vertical axis on the left is the mass specific capacity, in units of mAh g -1 , corresponding to the middle curve; the right ordinate is the Coulomb efficiency, corresponding to the upper curve in the figure. Figure 3 It can be seen that by coating the PDOL-1 electrolyte on the surface of the lithium negative electrode, the coulombic efficiency and cycle performance of the prepared Li@PDOL-1-S battery are greatly improved.

[0282] Figure 4 The SEM test results of the Li-Li symmetric battery of Example 13 after 50 charge and discharge cycles are shown in FIG. Figure 4 It can be seen that the lithium deposition on the surface of the lithium electrode is dense and uniform, and no obvious dendrites appear, indicating that the growth of lithium dendrites can be effectively inhibited after coating with PDOL-1.

[0283] Figure 5The SEM test results of the Li-Li symmetric battery of Comparative Example 2 after 50 charge and discharge cycles are shown in Figure 2. Figure 5 It can be seen that many fibrous lithium dendrites appear on the surface of the lithium electrode, indicating that the lithium negative electrode without PDOL-1 coating cannot inhibit the growth of lithium dendrites.

[0284] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. An electrolyte additive, characterized in that Including compounds shown in the following general structural formula Ⅰ, Ⅱ or Ⅲ: Wherein: R1, R2, R3 are each independently selected from a hydrocarbon or halogenated hydrocarbon containing at least one carbon atom; M is one of Zn, Sn, Si, Al, Ge and In; A is one of N, P, S, B, Cl, I and Br; D is one of O, F and Cl; n is any integer from 1 to 4.

2. The electrolyte additive according to claim 1, characterized in that The R1, R2 and R3 are independently selected from hydrocarbons or halogenated hydrocarbons and have 1-16 carbon atoms.

3. The electrolyte additive according to claim 1 or 2, characterized in that The general structural formula I includes at least one of the compounds shown in the following structures: The general structural formula II comprises at least one of the compounds represented by the following structures: Zn(ClO4)2, Zn(NO3)2 or Zn(BF4)2; and / or The general structural formula III includes at least one In(OOCCF3)4 or Zn(OOCCF3)2 of the compounds shown in the following structures.

4. An electrolyte, characterized in that The electrolyte comprises the electrolyte additive according to any one of claims 1 to 3 and an electrolyte salt.

5. The electrolyte according to claim 4, characterized in that The content of the electrolyte additive in the electrolyte is 0.1-30 wt %.

6. The electrolyte according to claim 5, characterized in that The electrolyte includes a polymer solid electrolyte, an organic-inorganic solid electrolyte and a liquid electrolyte.

7. The electrolyte according to claim 6, characterized in that The polymer solid electrolyte comprises one or two of poly 1,3-dioxolane and polyethylene oxide; the polymer solid electrolyte contains at least one of LiTFSI, LiFSI, LiNO3, LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiPF2, LiHFDF, NaTFSI, KTFSI and cyclic imide salts; and / or The organic-inorganic solid electrolyte includes one or two of PDOL-lithium dysprosium tantalum oxide solid electrolyte and PDOL-lithium lanthanum zirconium oxide; the organic-inorganic solid electrolyte contains at least one of LiTFSI, LiFSI, LiNO3, LiPF6, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiODFB, LiPF2, LiHFDF, NaTFSI, KTFSI and cyclic imide salts; and / or The solvent in the liquid electrolyte includes at least one of a fluorinated solvent, ethylene glycol dimethyl ether, dimethyl carbonate, 1,3-dioxolane, vinylene carbonate, propylene carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, propylene sulfite, methyl propionate, polyethylene oxide and dimethylacetamide, wherein the fluorinated solvent includes at least one of fluoroethylene carbonate, 3,3,3-trifluoroethyl methyl carbonate, 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether and tris(2,2,2-trifluoroethyl)phosphite.

8. The electrolyte according to claim 4, characterized in that The electrolyte salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium perchlorate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(monofluoromethylsulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide, sodium bis(trifluoromethylsulfonyl)imide, potassium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, potassium bis(fluorosulfonyl)imide, bis(trifluoromethanesulfonyl)imide, At least one of zinc sulfonyl imide, zinc bis(fluorosulfonyl)imide, sodium bis(fluorosulfonyl)imide, potassium bis(fluorosulfonyl)imide, zinc bis(trifluoromethanesulfonyl)imide, zinc bis(fluorosulfonyl)imide and cyclic imide salts; wherein the cyclic imide salt includes at least one of 1,1,2,2,3,3-hexafluoropropane-1,3-disulfonic acid imide lithium, 1,1,2,2-tetrafluoroethane-1,3-disulfonic acid imide lithium and 1,1,2,2,3,3,4,4-octafluorobutane-1,3-disulfonic acid imide lithium.

9. An electrolyte, characterized in that: The electrolyte comprises the electrolyte according to any one of claims 4 to 8.

10. A secondary battery, characterized in that: The invention comprises a negative electrode, a positive electrode, a separator and the electrolyte according to claim 9.

Citation Information

Patent Citations

  • Electrolyte for high-voltage lithium metal battery and preparation method of electrolyte

    CN115395097A

  • Electrolyte and battery containing same

    CN115863765A

  • Electrolyte, battery secondary liquid injection method and battery

    CN119050457A

  • Method and apparattus for validating noise classification result of resting-state functional magnetic resonance imaging

    KR1020250000546A